DemographIc changes and economic activity in the Vardar region - Daniloska Natasha; Boshkovska Diana (Institute of economics -Skopje, University „Ss. Cyril and Methodius“, 2024)
The results of the 2021 Census of Population, Households and dwellings showed that in the first decades of the 21st century in the Republic of North Macedonia, there was a decline in the total resident population and hinted at unfavorable demographic changes. These changes will undoubtedly have implications for the future development of the population, socio-economic and regional development. In this paper3, through available data from secondary sources, the Vardar region is analyzed as one of the eight non-administrative units-statistical regions in the Republic of North Macedonia. The available human resources and their economic characteristics (working age population and labor force) are perceived from the data of the two consecutive censuses 2002 and 2021. Also, some indicators of the economic activity of the Vardar region are analyzed (GDP per capita, GDP index, Gross value added by sectors of activity, Gross fixed capital formation by sector of activity and number of active enterprises) for the period 2010-2021. The identified changes of the basic demographic and socio-economic characteristics of the population and economic activity in the Vardar region can serve in the creation of appropriate policies, measures and activities for its development.
Keywords: Vardar region, population, demographic changes, socio-economic indicators